Gross and net production during the spring bloom along the Western Antarctic Peninsula. Issue 1 (7th November 2014) - Goldman, Johanna A. L.; Kranz, Sven A.; Young, Jodi N.; Tortell, Philippe D.; Stanley, Rachel H. R.; Bender, Michael L.; Morel, Francois M. M.
Summary: This study explores some of the physiological mechanisms responsible for high productivity near the shelf in the Western Antarctic Peninsula despite a short growing season and cold temperature. We measured gross and net primary production at Palmer Station during the summer of 2012/2013 via three different techniques: incubation with H2 18 O; incubation with 14 CO2 ; and in situ measurements of O2 /Ar and triple oxygen isotope. Additional laboratory experiments were performed with the psychrophilic diatom Fragilariopsis cylindrus . During the spring bloom, which accounted for more than half of the seasonal gross production at Palmer Station, the ratio of net‐to‐gross production reached a maximum greater than c . 60%, among the highest ever reported. The use of multiple techniques showed that these high ratios resulted from low heterotrophic respiration and very low daylight autotrophic respiration. Laboratory experiments revealed a similar ratio of net‐to‐gross O2 production in F. cylindrus and provided the first experimental evidence for an important level of cyclic electron flow (CEF) in this organism. The low ratio of community respiration to gross primary production observed during the bloom at Palmer Station may be characteristic of high latitude coastal ecosystems and partially supported by a very active CEF in psychrophilic phytoplankton.